(untitled) - Tokeshi, M. (Malden, MA, USA, 1999)
As a novel endeavour in ecological science, this book focuses on a major issue in organismal life on Earth:species coexistence. The book crosses the usual disciplinary boundaries between palaeobiology, ecology and evolutionary biology and provides a timely overview of the patterns and processes of species diversity and coexistence on a range of spatio-temporal scales. In this unique synthesis, the author offers a critical and penetrating examination of the concepts and models of coexistence and community structure, thus making a valuable contribution to the field of community ecology. There is an emphasis on clarity and accessibility without sacrificing scientific rigour, making this book suitable for both advanced students and individual researchers in ecology, palaeobiology and environmental and evolutionary biology.
Keywords: Sinh học môi trường,Hình thái,Biotic communities,Species